2015
DOI: 10.1080/10255842.2015.1051972
|View full text |Cite
|
Sign up to set email alerts
|

A dynamic multibody model of the physiological knee to predict internal loads during movement in gravitational field

Abstract: Obtaining tibio-femoral (TF) contact forces, ligament deformations and loads during daily life motor tasks would be useful to better understand the aetiopathogenesis of knee joint diseases or the effects of ligament reconstruction and knee arthroplasty. However, methods to obtain this information are either too simplified or too computationally demanding to be used for clinical application. A multibody dynamic model of the lower limb reproducing knee joint contact surfaces and ligaments was developed on the ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 34 publications
2
27
0
Order By: Relevance
“…The simulated knee forces in this article were quite close to the experimental results (cyan dash lines) obtained by Stylianou et al 32 until 60°knee flexion. Above that flexion level, the results tended to be much closer to experimental data (black dash lines) reported by Taylor et al 33 The results in this article were also generally consistent with the results calculated by Bersini et al 34 The results for the STKI are shown as black dotted lines in Figure 7. Above 50°knee flexion, the STKI resulted in smaller TF compressive forces than the CTKI.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The simulated knee forces in this article were quite close to the experimental results (cyan dash lines) obtained by Stylianou et al 32 until 60°knee flexion. Above that flexion level, the results tended to be much closer to experimental data (black dash lines) reported by Taylor et al 33 The results in this article were also generally consistent with the results calculated by Bersini et al 34 The results for the STKI are shown as black dotted lines in Figure 7. Above 50°knee flexion, the STKI resulted in smaller TF compressive forces than the CTKI.…”
Section: Resultssupporting
confidence: 91%
“…Above that flexion level, the results tended to be much closer to experimental data (black dash lines) reported by Taylor et al 33 . The results in this paper were also generally consistent with the results calculated by Bersini et al 34 . The results for the STKI are shown as black dotted lines in Fig.…”
Section: Figsupporting
confidence: 93%
See 1 more Smart Citation
“…As the Authors known, no studies addressed this topic and when the knee arthritis is localised at only one knee compartment, the surgical choice is generally driven by the orthopaedic surgeon experience. Results of Bersini 21 , that showed as the anterior fibres of ACL become inactive after 60° of knee flexion in conjunction with posterior cruciate ligament anterior bundle activation were deemed for the present study, relevant to suppose different strategies of squatting between TKA and UKA due to the different knee physiology, arthroplasty-related.…”
Section: Discussionmentioning
confidence: 99%
“…It is to be taken into account that neglection of deformations in some applications (e.g. simulation of implant-bone micromotions) might represent an unacceptable approximation, but nonetheless several outputs of interest in orthopedic applications (such as implant kinematics and contact forces) do not require a fully deformable model [5] : this method could thus represent a viable path to achieve the fast and overall accurate simulation tool sought, and it is indeed already used in many other engineering fields [6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%